Pengembangan Model Bahan Ajar Pembelajaran Bahasa pada Membaca Efektif Terintegrasi dengan Pendidikan Karakter di Era Merdeka Belajar - Albaburrahim, Albaburrahim; Rahman, Ainur (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The purpose of this study is to develop a model of language learning teaching materials that are integrated with character education, especially on the topic of effective reading in the era of independent learning. One of the causes of this condition is that reading is still monotonous and boring, and there is also a moral degradation of students in public life. So it is necessary to develop the effectiveness of Indonesian language learning in effective reading which is oriented to the character values of students. This research is a type of qualitative research with a descriptive approach. Data collection techniques using observation, interviews, and documentation. Data analysis by collaborating data with a model of teaching materials that combines character education. The results of this study indicate, namely: 1) the model of teaching materials based on the model of learning teaching materials that is developed effectively provides changes to the reading ability of students, (2) teaching materials based on the developed learning model will effectively develop the character of students during the reading learning process. in the era of independent learning.